2005
DOI: 10.3201/eid1110.041329
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilumin White-tailed Deer

Abstract: We examined the reservoir potential of white-tailed deer for Anaplasma phagocytophilum. Results suggest that white-tailed deer harbor a variant strain not associated with human infection, but contrary to published reports, white-tailed deer are not a reservoir for strains that cause human disease. These results will affect surveillance studies of vector and reservoir populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 12 publications
1
75
0
Order By: Relevance
“…While the white-footed mouse is likely the dominant small-mammal reservoir, infection is usually transient, unlike the chronic infection observed with B. burgdorferi (Goodman 2005). White-tailed deer are important for the maintenance of Ixodes populations, but the role these large mammals play in the life cycle of A. phagocytophilum is unclear (Massung et al 2005;Tate et al 2005;Rainwater et al 2006). White-tailed deer may be seropositive and/or PCR positive for A. phagocytophilum (Bouchard et al 2013).…”
Section: Human Granulocytic Anaplasmosis (Hga)mentioning
confidence: 99%
“…While the white-footed mouse is likely the dominant small-mammal reservoir, infection is usually transient, unlike the chronic infection observed with B. burgdorferi (Goodman 2005). White-tailed deer are important for the maintenance of Ixodes populations, but the role these large mammals play in the life cycle of A. phagocytophilum is unclear (Massung et al 2005;Tate et al 2005;Rainwater et al 2006). White-tailed deer may be seropositive and/or PCR positive for A. phagocytophilum (Bouchard et al 2013).…”
Section: Human Granulocytic Anaplasmosis (Hga)mentioning
confidence: 99%
“…32 In the same study, feeding adult ticks collected from deer were found to be infected with A. phagocytophilum-v1 more often than with A. phagocytophilum-ha. 32 However, it is unknown whether these infections were acquired from deer or another species during a previous blood meal.…”
Section: Discussionmentioning
confidence: 87%
“…42 In a previous study, blood from white-tailed deer was tested for the presence of the two strains 32 ; 11 of 38 deer were positive for A. phagocytophilumv1, whereas no A. phagocytophilum-ha was found in deer blood, suggesting that they can acquire A. phagocytophilumv1 but perhaps not A. phagocytophilum-ha. 32 In the same study, feeding adult ticks collected from deer were found to be infected with A. phagocytophilum-v1 more often than with A. phagocytophilum-ha. 32 However, it is unknown whether these infections were acquired from deer or another species during a previous blood meal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations